К проблеме определения актуальных онимов в фоновых знаниях носителей литовского и русского языка - Бирилло, Ж. Н. (Kalbotyra, 1994)
The problems of defining proper nouns in the background knowledge are considered in the article. The main attention here is given to the methods of selection of proper nouns to the description of these Obtained. A contrastive analysis was carried out to find similarities and distictions between the two groups (Lithuanian/Russian informant) of the proper nouns selected.